Matematyka
żanuśka
2021-04-08 16:28:54
Rozwiąż równanie (X-2) x (-3) x (-4) x (-5) = - 6000 X-niewiadoma x-razy, znak mnożenia
Odpowiedź
dofejkowaniatestowania
2021-04-08 17:32:19

mnożenie jest przemienne więc: (-3)x(-4)x(-5)x(X-2)=-6000 (-60)x(X-2)=6000 -60X+120=6000 -60X=6000-120 -60X=5880 /(-60) X=-98  :)

dopati
2021-04-08 17:33:34

(x-2)*(-3)*(-4)*(-5)=-6000x (-3x+6)*(-4)*(-5)=-6000x (12x-24)*(-5)=-6000x -60x+120=-6000x 120=-6000x-60x    /:(-6060) -0,0198=x *-mnożenie

Dodaj swoją odpowiedź